Leaching characterization of dry flue gas desulfurization materials produced from different flue gas sources in China. (15th September 2017) - Cheng, Chin-Min; Amaya, Maria; Lin, Shanshan; Su, Qingfa; Wu, Muh-Cheng; Butalia, Tarunjit; Wolfe, William
Highlights: Leaching behaviors of DFGD materials from major sources in China were tested. B, Mo and Se are the most readily leachable COCs under percolation scenarios. Cr and Tl showed the highest cumulative releases among COCs under diffusion. Abstract: By-products produced from dry flue gas desulfurization (DFGD) have been used in many engineering applications. Structural fill and/or mine reclamation applications utilize more than 74 and 22% of the annual DFGD production in Europe and the United States, respectively. In China, although there are reports showing the applications of DFGD materials in the production of bricks, precast concrete, highway construction, and agricultural applications, large-scale, high-volume uses have developed slowly. One of the major roadblocks to high-volume utilization is lack of knowledge regarding the associated utilization issues. In order to better understand the environmental response of Chinese DFGD materials, this study compared the leaching characteristics of three typical DFGD materials produced from different flue gas sources (i.e., coal-fired boiler, iron and steel sintering plant, and circulating fluidized bed (CFB) boiler). The goal of this study is to characterize the release of inorganic constituents of concern (COCs) under the leaching conditions (i.e., pH dependence, percolation column, and diffusion-controlled conditions) representing different potential application scenarios. Except for Se, the maximum concentrations of all selected COCs (Hg, B, Mo, As, Ba, Cd, Cr, Pb, Sb, Co, and Tl) under all tested leaching conditions were lower than the toxicity levels. The high release of Se observed under acidic conditions in the pH-dependent leaching tests might be adversely promoted by nitric acid induced oxidation of sparingly soluble selenite minerals to soluble selenate counterparts. Rapid initial releases of Mo, Se, B, and Tl were found during the early stages of the percolation column leaching tests. B, Mo and Se were found to be the most readily leachable COCs under the scenarios when the leaching is equilibrium-controlled. Under a diffusion-controlled leaching environment, Cr and Tl showed the highest cumulative mass release among the COCs.